Penelusuran Naskah-naskah Ulu-Islam Pusaka Keluarga/Desa di Provinsi Bengkulu Tracing the Ulu-Islamic manuscripts of Family/Village Heirlooms in Bengkulu Province - Sarwit Sarwono (MOZAIK HUMANIORA, 2019)
Abstract            This study was intended to identify and describe the ulu-Islamic texts stored as village or family heirlooms in the Bengkulu Province. Research based on philology by utilizing the principles of text analysis. The collection of research materials was carried out through surveys in 19 villages, spread in Kaur Regency (2 villages), South Bengkulu Regency (3 villages), Seluma District (10 villages), Lebong District (1 village), Rejang Lebong District (1 village) , North Bengkulu Regency (1 village), and Bengkulu City (1 village). The survey found 74 ulu texts. Of that number, seven texts were identified as ulu-Islam texts, namely 1 manuscript belonging to the Bahud family (BAH-01), 2 manuscripts belonging to the Jalil family (JAL-01 and JAL-02), and 4 manuscripts belonging to the Asrip family (ASR-01 , ASR-02, ASR-03, and ASR-04). The manuscripts are made entirely of striped paper and books. Based on the text content, as well as the codex aspects, it can be stated that in its development, the ulu writing tradition in Bengkulu had taken part in the in the process of production and distribution of Sufism and tarekat texts, until about the end of the first half of the twentieth century. Furthermore, the absence of the phenomenon of text transmission shows that Islamic knowledge in the ulu manuscripts was taken place through the transformation of texts. The text is written based on the author;s knowledge and experience of Sufism and the practice of the tarekat. This phenomenon also shows that the spread of Islam in Bengkulu enters and integrates with local traditions and culture.